Synthetic nanocomposite MgH2/5 wt. % TiMn2 powders for solid-hydrogen storage tank integrated with PEM fuel cell - M. Sherif El-Eskandarany (Nature Portfolio, 2017)
Abstract Storing hydrogen gas into cylinders under high pressure of 350 bar is not safe and still needs many intensive studies dedic ated for tank’s manufacturing. Liquid hydrogen faces also severe practical difficulties due to its very low density, leading to larger fuel tanks three times larger than traditional gasoline tank. Moreover, converting hydrogen gas into liquid phase is not an economic process since it consumes high energy needed to cool down the gas temperature to −252.8 °C. One practical solution is storing hydrogen gas in metal lattice such as Mg powder and its nanocomposites in the form of MgH2. There are two major issues should be solved first. One related to MgH2 in which its inherent poor hydrogenation/dehydrogenation kinetics and high thermal stability must be improved. Secondly, related to providing a safe tank. Here we have succeeded to prepare a new binary system of MgH2/5 wt. % TiMn2 nanocomposite powder that show excellent hydrogenation/dehydrogenation behavior at relatively low temperature (250 °C) with long cycle-life-time (1400 h). Moreover, a simple hydrogen storage tank filled with our synthetic nanocomposite powders was designed and tested in electrical charging a battery of a cell phone device at 180 °C through a commercial fuel cell.